FEATURES OF THE CLINICAL MANIFESTATIONS OF AUTOIMMUNE OPTIC NEUROPATHY IN MULTIPLE SCLEROSIS ON CORTICOSTEROID THERAPY - Dalia Sharliz Raihana; Lukisiari Agustini; Deasy Fetarayani (Majalah Biomorfologi, 2024)
Highlights Intravenous corticosteroid treatment followed by oral clinical treatment can reduce the incidence of post-treatment optic neuritis recurrenc Visual acquisition increases at one-month post-treatment.   Abstract Background: The clinical picture of autoimmune optic neuropathy, known as neuritis, is strongly influenced by the unique structure of the human anterior visual pathway. The central nervous system autoimmune is related to multiple sclerosis (MS). Optic neuropathy is an injury that frequently results in acute inflammatory damage. Objective: This study aimed to determine the clinical manifestations of autoimmune optic neuropathy in multiple sclerosis and identify diseases with appropriate corticosteroid therapy using systematic review methods. Material and Method: This study used a systematic review method to analyze topic-related kinds of literature on  Scopus, PubMed, and Google Scholar databases. The literature screening process was carried out based on the PRISMA 2020 guidelines. Result: Regarding the post-treatment recurrence rate of optic neuritis, the use of intravenous corticosteroids alone and intravenous corticosteroid followed by oral administration may clinically reduce the incidence of recurrence in the patients compared those receiving placebo and oral administration. This suggests that intravenous corticosteroid followed by oral corticosteroid treatment is effective in helping to reduce the incidence of recurring optic neuritis. Conclusion: Intravenous corticosteroid treatment followed by oral administration may clinically reduce the incidence of post-treatment recurrence of optic neuritis in multiple sclerosis (MS) patients.